2022
DOI: 10.1111/jcal.12725
|View full text |Cite
|
Sign up to set email alerts
|

Integrating instructional designs of personalized learning through the lens of universal design for learning

Abstract: Background: Personalized learning (PL), conceptualized as an education innovation that tailors learning to meet diverse student needs, has drawn increased attention from different fields of study, such as education, learning sciences, and computer science. Regardless, there is a lack of a comprehensive understanding of PL instructional designs supported by technology.Objectives: This systematic literature review aimed to provide an empirical integration of PL designs and implementation across disciplines throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
0
1
0
1
Order By: Relevance
“…Since adaptive learning is flexible and relies on a pattern of outcome-based thinking (Narvaez & Reyes, 2022), in which facts and concepts are connected, manipulated, categorised and combined with invention, and information and intellect are combined to provide new answers to old issues in an appropriate environment (Ichsan et al, 2019;Zhang et al, 2022). Technology acceptance (Balyer, 2018;Lu et al, 2021) is also detrimental effect because the information found online is not necessarily valid.…”
Section: Adaptive Learning Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since adaptive learning is flexible and relies on a pattern of outcome-based thinking (Narvaez & Reyes, 2022), in which facts and concepts are connected, manipulated, categorised and combined with invention, and information and intellect are combined to provide new answers to old issues in an appropriate environment (Ichsan et al, 2019;Zhang et al, 2022). Technology acceptance (Balyer, 2018;Lu et al, 2021) is also detrimental effect because the information found online is not necessarily valid.…”
Section: Adaptive Learning Skillsmentioning
confidence: 99%
“…As an effective IDC pedagogical management tool, the PAL provides affective, psychological and cognitive resources to support learners (Zhou & Wang, 2019). Adaptive interaction, which is the fundamental basis of this pedagogy, is extremely beneficial for learners (Zhang et al, 2022). Therefore, an adequate level of PAL's reliability of Cronbach's Alpha (>.85) and validity of KMO (>.80) (Midgley et al, 1998) was used in this study.…”
Section: Measurement Of Adaptive Learning Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed research gives valuable insights for developing practical aspects for personalized learning environments: layout presentation, customized learning materials, learning styles, and preferences [50]. According to a recent survey on adaptive, personalized learning systems, PL models present layouts and study materials with the following four essential components: students profiles that map out each student's unique set of skills, interests, and aspirations; individualized learning plans that are adapted to each student's unique trajectory; a focus on mastering customized subjects and assessment for skills growth; adaptable learning environments which is accessible anywhere and anytime, which also consider individualized learning styles and preferences [51]. The PL systems make it easier to deliver teaching and learning subject matter based on the needs of the learners.…”
Section: Personalized Adaptive Learning Systems Environmentmentioning
confidence: 99%
“…• Proporcionar múltiples formas de acción y expresión En la actualidad, disponemos del modelo 2.2 de las pautas del DUA que nos sirven de base y nos orientan para programar nuestras clases con garantías de flexibilidad, variabilidad y apoyo a la diversidad presente en las aulas (Zhang, et al, 2022).…”
Section: Contextualizando El Diseño Universal Para El Aprendizajeunclassified